Omitting radiation therapy in women with triple-negative breast cancer leads to worse breast cancer-specific survival. (April 2017) - Kindts, I.; Buelens, P.; Laenen, A.; Van Limbergen, E.; Janssen, H.; Wildiers, H.; Weltens, C.
Abstract: Purpose: To examine locoregional recurrence (LRR) and breast cancer-specific survival (BCSS) after breast-conserving therapy (BCT) or mastectomy (ME) with or without radiation therapy (RT) in triple-negative breast cancer (TNBC). Material & Methods: We identified non-metastatic TNBC cases from a single institution database. BCT, ME with RT (ME + RT) and ME only were compared with respect to LRR and BCSS. Cox regression models were used to analyze the association between prognostic factors and outcome. Results: 439 patients fulfilled the inclusion criteria. Median follow-up was 10.2 years (interquartile range 7.9; 12.4 years). Patients in the BCT (n = 239), ME + RT (n = 116) and ME only (n = 84) group differed with respect to age, pT, pN, lymphovascular invasion, lymph node dissection and chemotherapy administration. Ten-year LRR rates were seven percent, three percent and eight percent for the BCT, ME + RT and ME only group, respectively. pN was associated with LRR. In multivariable analysis LRR were significantly lower in the ME + RT group compared to the BCT and the ME only group (p 0.037 and 0.020, respectively). Ten year BCSS was 87%, 84% and 75% for the BCT, ME + RT and ME only group, respectively. pT, pN, lymph node dissection, lymphovascular invasion and the administration of chemotherapy were associated with BCSS. In multivariable analysis BCSS was significantly lower in the ME only group compared to the BCT group and the ME + RT group (p 0.047 and 0.003, respectively). Conclusion: TNBC patients treated with ME without adjuvant RT showed significant lower BCSS compared to patients treated with BCT or ME + RT and significant more LRR compared to ME + RT when corrected for known clinicopathological prognostic factors. Highlights: Triple-negative breast cancer patients were evaluated with respect to LRR and BCSS. LRR were significantly lower in the ME + RT group compared to the BCT and the ME only group. BCSS was significantly lower in the ME only group compared to the BCT group and the ME + RT group.